Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/10942912.2019.1590396
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds Responsible for Antioxidant Activity of Different Varieties of Date ( Phoenix dactylifera L.) Elucidated by 1 H- NMR Based Metabolomics

Abstract: Several studies have demonstrated strong antioxidant activity of date fruits. Nevertheless, limited data is available for the bioactive compounds responsible for the activity. In this study, the antioxidant activity of five different date varieties (Ajwa, Anbara, Piyarom, Rabbi and Deglet Nour) extracted using 80% ethanol was determined using free radical scavenging (DPPH), ferric reducing power (FRAP) and antioxidant capacity (ABTS) assays. The 1 H-NMR was employed to profile the bioactive metabolites present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…One of the main properties of polyphenols is their antiradical activity which is itself attributed to their hydroxyl groups which contribute to their redox properties, electron-donating capacity, singlet antioxygen action, and metal chelating capacity. Indeed, the class of polyphenols has been proven to determine the free radical scavenging activity, the flavones being the most effective [ 41 ]. This result was corroborated by Nahak et al [ 42 ] who showed that an antioxidant that is effective in one test is not necessarily effective in another on the one hand.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main properties of polyphenols is their antiradical activity which is itself attributed to their hydroxyl groups which contribute to their redox properties, electron-donating capacity, singlet antioxygen action, and metal chelating capacity. Indeed, the class of polyphenols has been proven to determine the free radical scavenging activity, the flavones being the most effective [ 41 ]. This result was corroborated by Nahak et al [ 42 ] who showed that an antioxidant that is effective in one test is not necessarily effective in another on the one hand.…”
Section: Discussionmentioning
confidence: 99%
“…A very weak correlation with polyphenols content (r 2 = 0.09, P = .93) was observed, which is in contrast to many works generally linking both parameters [31,32], and which therefore questions the nature of polyphenols that are present in the extract. Indeed, the class of polyphenols has been proven to determine the free radical scavenging activity, the flavanols being the most effective [31,33]. These flavonols were not detected in Lophira procera barks aqueous extract [27].…”
Section: Discussionmentioning
confidence: 99%
“…That compound might be flavonoids as it showed the highest correlation with the total antioxidant capacity (r 2 = 1.00, P = .01) and the iron-reducing capacity (r 2 = 0.94, P = .22). It can, therefore, be suggested a quantitative dependence of TAC with flavonoids and tannins but rather a qualitative one (nature of the compounds) with polyphenols and alkaloids [33,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The high antifungal and antibacterial activities of date fruit extract could be a result of their high content of free and bound polyphenols [19]. Date fruit extract was reported for it is strong antimicrobial activity due to the high phenolic compounds content determined using 1 H-NMR analysis [20]. However, very limited studies investigated the potential applications of date fruit as functional ingredient in making bakeries and confectionaries.…”
Section: Antifungal Activity Of Fermented Date Fruitmentioning
confidence: 99%